The Angular Distribution of Lower Band Chorus Waves Near Plasmaspheric Plumes. Issue 9 (7th May 2022) - Hartley, D. P.; Chen, L.; Christopher, I. W.; Kletzing, C. A.; Santolik, O.; Li, W.; Shi, R.
Abstract: Plumes have been identified as an access region for chorus waves to enter the plasmasphere. Here, for the first time, chorus wave properties are parameterized by distance from the plume boundary. Case studies and statistical analysis indicate that the polar wave vector angle, θ k, of chorus becomes more oblique near the plume edge. Occurrence rates of θ k > 35° on the plume boundary are approximately double that observed further away from the plume. Whilst the increase in θ k is apparent on both plume edges, the distribution of θ k exhibits different behavior between the Eastward and Westward boundaries. In general, the distribution of azimuthal wave vector angles, ϕ k, is symmetric about the anti‐Earthwards direction. However, near the Eastward plume boundary, an Eastwards skew of ϕ k is reported. This result provides new insight on chorus propagation in the context of the chorus‐to‐hiss mechanism, and has implications for quantifying wave‐particle interactions in the near‐plume region. Plain Language Summary: Chorus wave properties are typically parameterized spatially in magnetic coordinates. Here, for the first time, we specifically study chorus wave vector characteristics near density enhancements known as plasmaspheric plumes, which have been identified as an access region for chorus waves to enter the plasmasphere. It is found that chorus waves propagate at larger angles with respect to the background magnetic field directly on the boundary of high‐density plume structures. This behavior is reported on both the Eastward and Westward plume edges, yet the variations in the distribution of wave vector angles is reported to be different between the Eastwards and Westwards edge. In general, it is found that the wave vector, k, is distributed symmetrically about the anti‐Earthwards direction, however, near the Eastwards plume boundary an Eastwards skew is reported. These results shed new light on the propagation of chorus waves near plasmaspheric plumes, which is important for modeling the propagation of waves into the plasmasphere, as well as for modeling interactions between waves and particles in this region. Key Points: Lower band chorus waves are shown to be more oblique near the boundaries of plasmaspheric plumes, particularly for frequencies below 0.25 f ce Wave vector distribution shows clear differences between Eastward and Westward plume boundaries, despite increase in obliquity on both edges Azimuthal wave vector angle is generally symmetric about anti‐Earthwards direction, yet Eastwards skew is reported near Eastward plume edge